Chagas' disease: selective affinity and cytotoxicity of Trypanosoma cruzi-immune lymphocytes to parasympathetic ganglion cells - Maria Lúcia Teixeira; Jofre Rezende Filho; Florêncio Figueredo; Antonio R. L. Teixeira (Memorias do Instituto Oswaldo Cruz, 1980)
The megaesophagus and megacolon endemic in South America are related , to Chagas' disease. These mega conditions are found in patients with chronic Chagas's infection, when the parasite is not demonstrable in the lesions. These are characterized by depopulation of parasympathetic ganglion cells, dilation and hypertrophy of the viscera. In the experiments described here we deminstrate a selective affinity and adherence of Trypanosoma cruzi-immune lymphocytes to myenteric, parasympathetic ganglion cells, leading to neuronolysis. None of these features are observed when non-immune lymphocytes from control rabbits are used, or when the immune lymphocytes are allowed to react with CNS neurons. This demonstration is an indication of the high degree of specificity of the destruction of parasympathetic neurons in Chagas' disease. We postulate that the T. cruzi-immune lymphocyte rejection of parasympathetic neurons, but not of CNS neurons, might be related to recognition of a cross-reacting antigenic determinant secreted only by the target neurons. In favor of this interpretation is the observation of lymphocytic infiltrates and parasympathetic ganglion cell destruction in chronic Chagas' infection in the absence of encephalitis. O megaesôfago e o megacolon endêmicos na América do Sul estão relacionados á doença de Chagas. Estas condições clínicas são encontradas em pacientes com infecção chagásica crônica, quando o parasito não é demonstrado nas lesões caracterizadas por povoamento de células neuronais parassimpáticas. Nos experimentos descritos aqui nós demonstramos uma afinidade seletiva de linfócitos imunes, sensibilizados pelo T. cruzi, para neurônios de gânglios mioentéricos. Os linfócitos imunes citotóxicos aderem nas células ganglionares, produzindo neuronólise. Isto não se observa quando linfócitos não-imunes são usados, ou quando os linfócitos imunes são colocados na presença de neurônios do sistema nervoso central. Esta é uma demonstração do alto grau de especificidade da destruição de neurônios parassimpáticos na doença de Chagas. Postulamos que a rejeição de neurônios parassimpáticos deve estar relacionada ao conhecimento de um determinante antigênico de reação cruzada, o qual seria secretado exclusivamente pelos neurônios parassimpáticos. Em favor desta interpretação temos a observação de infiltrados linfocitários com destruição de células ganglionares parassimpáticas em pacientes com infecção chagástica crônica, na ausência de encefalite.